Ennio Morricone's Film Music in the Western Genre - Maloney, Hugh B J (2024)
This thesis conducts an appraisal and analysis of the western-genre film music of Ennio Morricone (1928–2020), as composed for 34 features released between 1963 and 2015. It ascertains the fundamental compositional characteristics of this body of work, while drawing out their salience against a range of historical and theoretical contexts: music in the western, Italian cinema, Morricone’s life and wider practice, and film-scoring technique. Beyond the necessary outlining of contextual developments and a largely chronological survey of the works that play host to Morricone’s engagement with the genre, the enquiry is thematically structured, exploring the nature and significance of these characteristics as they manifest within the filmography. The essential aim of the study is to understand Morricone’s relationship with the genre. While this is a notion conventionally alluded to in discussions of Sergio Leone’s cinema, the thesis expands the discourse beyond this limited filmography to include the entirety of Morricone’s experience composing music for westerns, putting the composer’s practice front and centre.